Effect of Mg Content and Heat Treatment on the Mechanical Properties of Low Pressure Die-Cast 380 Alloy - S. Morin; E. M. Elgallad; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering)
The present study was carried out on a 380 alloy containing 9.13% Si, 3.22% Cu, 1.01% Fe, 0.06% Mg, 0.16% Mn, and 2.28% Zn. The magnesium level was increased to 0.3 and 0.55%, by adding pure Mg to the melt. Tensile and fatigue samples were produced using low pressure die casting. The results show that the average dendrite arm spacing was about 6 μm. Increasing the amount of Mg from 0.06% to 0.55% increased the volume fraction of π-Al8Mg3FeSi6 and Q-Al5Cu2Mg8Si6 phases from 0.8% to 1.7%. Following solutionizing at 490°C for 8 h, the maximum ultimate tensile strength was obtained from alloys containing 0.3% Mg. Further increases in Mg content resulted in an increase in the amount of insoluble intermetallics and, hence, low tensile strength. Aging at 155°C for times up to 25 h resulted in a linear increase in the alloy strength regardless of the amount of added Mg. Aging at 220°C, however, revealed multiple peaks corresponding to the precipitation of various phases. A good relation between the applied force and the number of cycles prior to failure was established. The alloy containing 0.3% Mg produced the best fatigue resistance. The effect of porosity was more pronounced on the fatigue samples than on the tensile bars.